A note on the Riemann ξ-function - Garunkštis, Ramūnas (Lietuvos matematikos rinkinys, 2000)
We prove that for σ > 4.5, inf ℜ(ξ’(σ + it)/ξ(σ + it) ) : - ∞ < t < ∞ = ξ’(σ)/ξ(σ). This improves the result obtained by Lagarias.